Image quality in pediatric imaging in association with use of sedation and general anesthesia - Ab. Hamid, Suzana; M., Roziah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2007)
Introduction: The accuracy of image interpretations of CT and MRI studies is absolutely dependent on the quality of the images produced. Motion artifacts which result from the patients' movement during image acquisitions may lead to misinterpretation, wrong diagnosis or inconclusive examinations. In pediatric age groups, most of CT and MRI examinations require sedation or general anesthesia to achieve the degree of cooperation or immobilisation to complete the procedures successfully. Methods: The patients were randomly chosen among children, from newborn to 12 years of age who underwent sedation and general anesthesia for CT scan and MRI in the University of Malaya Medical Centre between September 2001 and August 2003. The quality of MRI and CT images were evaluated by radiologists using a three-point scale: 1- no motion artifact; 2- minor motion artifacts and 3- major motion artifacts. Results: Among sedated children, 75.5% and 41% had good CT and MRI images respectively. In general, the anesthesia group, 100% had good CT images and 85.7% had good MRI images. Children who received sedation (33.5%) had severe motion artifacts whereas none of the anesthetised children had severe motion artifacts. Conclusion: General anesthesia is much better for good quality images in both MRI and CT examinations; however it is associated with a higher cost and longer hospital stay. Combination of oral chloral hydrate and intravenous midazolam was found to be the most effective sedative agent in terms of CT/MRI image quality.